Tannin-rich pigments for improvement of electrochemical properties of anticorrosive paint systems - Hadzich Girola, Antonella; Obregón Valencia, Daniel Cristopher; Flores Merino, Santiago; Romagnoli, R.; Di Sarli, A.R. (Springer, 2025)
Hydrolysable tannins are natural polyphenols susceptible to hydrolysis that can be extracted from different vegetable plants. Tara pods, of Peruvian origin, concentrate a high tannin content and, besides their low exploitation impact, their tannin extract has shown high potential industrial applications due to their ability to form complexes with a broad variety of metal ions. However, developing an anticorrosive pigment of low-cost, high efficiency and reduced environmental impact is still a challenge. Herein, tannin-rich pigments were synthesized with Tara powder and zinc ions to produce metallic complexes known as tannates for corrosion protection. The anticorrosive behavior of zinc tannates was studied by direct current electrochemical techniques on pigment extracts and electrochemical impedance spectroscopy tests by analyzing pigmented primers and painting systems. Scanning electron microscopy and energy dispersive analysis were performed to study the protective layers morphology. Results indicated that zinc tannates inhibit satisfactorily steel corrosion overcoming the recognized behaviour of conventional pigments. As part of a painting system, alkyd primers with zinc tannates presented the best inhibitory properties. Zinc tannates could have the necessary requirements to be considered anticorrosive pigments, becoming a green alternative for corrosion prevention.
Keywords: EIS; Polarization; Paint coatings; SEM; Tannins; Zinc tannate; Taninos--Aplicaciones industriales; Tanatos; Revestimientos de cinc; https://purl.org/pe-repo/ocde/ford#2.04.01